How Do Axial Scan Orientation Deviations Affect the Measurements of Knee Anatomical Parameters Associated with Patellofemoral Instability? A Simulated Computed Tomography Study - Xiong, Ran; Chen, Cheng; Yin, Li; Gong, Xiaoyuan; Luo, Jiangming; Wang, Fuyou; Yang, Liu; Guo, Lin (The Journal of Knee Surgery, 2018)
The purpose of this study was to detect the correlation between axial scan orientation discrepancy and the knee anatomical parameters associated with patellofemoral instability during computed tomography (CT) scanning. CT scan data of 16 knees from 16 healthy subjects were retrieved. The reslicing processes were performed to simulate different axial scan orientations generated due to leg adduction/abduction during CT scanning. Eight parameters (tibial tubercle to trochlear groove [TT-TG], tibial tubercle to posterior cruciate ligament [TT-PCL], patellar tilt, lateral trochlear inclination, sulcus angle, trochlear depth, trochlear facet asymmetry, and trochlear condyle asymmetry) of five angles (neutral zero, 4/8 degrees of adduction and 4/8 degrees abduction) were quantified. All eight parameters showed varying degrees of deviations to the different axial scan orientations. TT-TG, patellar tilt, lateral trochlear inclination, and trochlear condyle asymmetry were relatively sensitive to axial scan orientation changes, whereas TT-PCL, sulcus angle, trochlear depth, and trochlear facet asymmetry were relatively insensitive. Although the sensitivities are various, surgeons should be aware of this situation and make necessary corrections.
Keywords: knee; patellofemoral instability; CT; axial scan orientation; anatomical measurement